Spodoptera frugiperda and corn yield control by liquid fertilizers and insecticides - Díaz-Chuquizuta, Percy; Hidalgo-Meléndez, Edison; Aguirre-Gil, Oniel Jeremías; Valdés-Rodríguez, Ofelia Andrea (Ecosistemas y Recursos Agropecuarios, 2022)
.This study aims to determine the response of Spodoptera frugiperda and corn yield to the applications of bovine liquid fertilizer (Biol) mixed with biologic or synthetic insecticides. A complete randomized block design composed of eight treatments (control, Biol, Beauveria bassiana, Neem oil, Spinosad, Biol with B. bassiana, Biol with Neem oil, and Biol with Spinosad) was used. Data was analyzed by ANOVA and media comparisons by the Tukey method (p ≤ 0.05). The lowest percentages of incidence of S. frugiperda were obtained with the application of Spinosad (20.40%) and Biol with Spinosad (12.87%), while the control had 65.86% of incidence (p < 0.05). The highest average corn yields were obtained with Neem oil, Biol, Biol with B. bassiana, and Biol with Neem oil, achieving 8.15, 7.97, 7.52, and 7.37 t ha−1, respectively.